Sosialisasi Prinsip Keselamatan Transportasi Masyarakat Perkotaan untuk Mewujudkan Kota Ramah Mobilitas - Indriaty Wulansari (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The rapid growth of motorized vehicles in urban areas poses significant challenges to transportation safety and the overall comfort of public mobility. Makassar City, as one of Indonesia’s major metropolitan areas, faces an increasing risk of traffic accidents due to road congestion, unsafe user behavior, and limited pedestrian- and cyclist-friendly infrastructure. This community service program aims to enhance public awareness and understanding of transportation safety principles through participatory community-based socialization. The implementation methods include field surveys, development of educational materials, interactive workshops, simulation of proper traffic facility use, and evaluation of participants’ knowledge through pre- and post-tests. The activities were conducted at several strategic locations in Makassar City and involved one hundred participants from diverse backgrounds. The results indicate a significant improvement in participants’ knowledge and safe behavior, both as drivers and pedestrians, after attending the program. The community showed greater awareness of using pedestrian crossings, safety equipment, and traffic ethics. This initiative has proven effective in fostering a culture of safety in urban environments and represents an important step toward achieving a safer, more inclusive, and mobility-friendly city for all road users.